The Influence Of E-Service Quality, E-Trust, And Perceived Value On Customer Loyalty Through Customer Satisfaction Of Alfagift Application By Alfamart In Indonesia - Meileny S.A.B, Findy; Maya Ariyanti, S., M.M, Dr. (International Journal of Science, Technology & Management, 2024)
The purpose of this study is to identify some significant effects of perceived value, e-trust, and e-service quality on customer loyalty through customer satisfaction of Alfagift in Indonesia. This research includes quantitative research using questionnaires data collection methods. The researcher had sent online questionnaires to 155 respondents and non probability purposive sampling was used in this study. The data analysis technique used is SEM with the Smart PLS application. The results of the statistical analysis shows that there is a significant impact of customer satisfaction with Alfagift on customer loyalty. Whereas. Alfagift's customer satisfaction is determined by factors such as perceived value, e-trust, and e-service quality that consumers experience while utilizing the program. Eventually, if the user is satisfied with the application's support, they will likely remain faithful to Alfagift. In addition, the customer loyalty of Alfagift users is significantly impacted by e-service quality, e-trust, and perceived value through customer satisfaction.